2021
DOI: 10.1186/s12872-021-02293-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and trends of coronary artery disease risk factors and their effect on age of diagnosis in patients with established coronary artery disease: Tehran Heart Center (2005–2015)

Abstract: Background Coronary artery disease (CAD) is a universal public health challenge, more prominently so in the low- and middle-income countries. In this study, we aimed to determine prevalence and trends of CAD risk factors in patients with documented CAD and to determine their effects on the age of CAD diagnosis. Materials and methods We conducted a registry-based, serial cross-sectional study using the coronary angiography data bank of the Tehran He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
4
14
0
2
Order By: Relevance
“…Preoperative variables consisted of serum hemoglobin (Hb), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C), total cholesterol, triglycerides (TG), creatinine (Cr), left ventricular ejection fraction (EF), diabetes, hypertension, opium consumption, smoking status, prior myocardial infarction (MI), preoperative heart failure (HF), and chronic obstructive pulmonary disease (COPD). The definitions were consistent with prior studies on this population (9). Perioperative variables, including cardiopulmonary pump utilization and ventilation hours, were assessed.…”
Section: Variables and Outcomesmentioning
confidence: 98%
“…Preoperative variables consisted of serum hemoglobin (Hb), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C), total cholesterol, triglycerides (TG), creatinine (Cr), left ventricular ejection fraction (EF), diabetes, hypertension, opium consumption, smoking status, prior myocardial infarction (MI), preoperative heart failure (HF), and chronic obstructive pulmonary disease (COPD). The definitions were consistent with prior studies on this population (9). Perioperative variables, including cardiopulmonary pump utilization and ventilation hours, were assessed.…”
Section: Variables and Outcomesmentioning
confidence: 98%
“…The first 4 risk factors have long been reported and proven to be risk factors for CAS. [ 26 , 27 ] Regarding BE with CAS in patients with RGERD, few studies have reported BE alone until now. Our previous study reported that GERD is very common in patients with CAD and refractory chest pain, and 49% of chest pain is associated with acid reflux due to GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Global incidence of CAD is increasing day by day. 12,13 There are tons of evidence that revascularization can help to return contractile function in presence of viable, ischemic and dysfunction myocardium. Patients with severely reduced LV systolic function but viable myocardium are still candidates of revascularization rather than cardiac transplantation.…”
Section: Discussionmentioning
confidence: 99%